Multiplanar knee kinematics-based test battery helpfully guide return-to-sports decision-making after anterior cruciate ligament reconstruction - Zhou, Lan; Xu, Yihong; Zhang, Jing; Guo, Luqi; Zhou, Tianping; Wang, Shaobai; Xu, Weidong (Frontiers in Bioengineering and Biotechnology, 2022)
Background: There are currently no well-established criteria to guide return to sports (RTS) after anterior cruciate ligament reconstruction (ACLR). In this study, a new test battery consisting of subjective and objective tests, especially multiplanar knee kinematics assessment, was developed to aid RTS decision making after ACLR. Methods: This study was conducted with 30 patients who were assessed a mean of 9.2 ± 0.5 months after ACLR. All patients underwent complete evaluations of both lower limbs with four objective assessments [isokinetic, hop, knee laxity, and 6–degree of freedom (6DOF, angle: flexion-extension, varus-valgus, internal-external rotation; translation: anteroposterior, proximodistal, mediolateral) knee kinematics tests] and two subjective assessments [International Knee Documentation Committee (IKDC) and Anterior Cruciate Ligament Return to Sport after Injury (ACL-RSI) questionnaires]. Limb symmetry indices (LSIs) of knee strength, hop distance, and range of motion (ROM) of knee kinematics were calculated. LSI ≥ 90%, IKDC scale score within the 15th percentile for healthy adults, and ACL-RSI score > 56 were defined as RTS criteria. Results: Significant differences between affected and contralateral knees were observed in the quadriceps strength (P < 0.001), hamstring strength (P = 0.001), single hop distance (P < 0.001), triple hop distance (P < 0.001), and rotational ROM (P = 0.01). Only four patients fulfilled the overall RTS criteria. The percentages of patients fulfilling individual criteria were: quadriceps strength, 40%; hamstring strength, 40%; single hop distance, 30%; triple hop distance, 36.7%; knee ligament laxity, 80%; flexion-extension, 23.3%; varus-valgus rotation, 20%; internal-external rotation, 66.7%; anteroposterior translation, 20%; proximodistal translation, 33.3%; mediolateral translation, 26.7%; IKDC scale score, 53.3%; and ACL-RSI score, 33.3%. Conclusion: At an average of 9 months after ACLR, objectively and subjectively measured knee functional performance was generally unsatisfactory especially the recovery of knee kinematics, which is an important prerequisite for RTS.